Sacrificed at the Alamo Tragedy and Triumph in the Texas Revolution. - Winders, Richard Bruce (Military history of Texas series., 2020)
The Battle of the Alamo is one of the most compelling stories from American history. Students of the battle often wonder why William B. Travis and his small garrison were left alone to meet their fate at the hands of General Santa Anna. Author Richard B. Winders, the historian and curator at the Alamo, examines events that led to this epic struggle and concludes that in-fighting among the revolutionary leadership doomed the Alamo garrison.The Texan victories of 1835 created discord among rebel leaders as various factions strove to direct the revolution to meet their own specific goals. That bickering resulted in an almost total breakdown of Texan military forces as individual commands were swept into the political battle. The democratic fervor of the 1830s worked against building a cohesive Texan Army and was largely responsible for the twin tragedies of the Alamo and Goliad.?Informative and provocative, Sacrificed at the Alamo will appeal to general readers as well as students of the classic battle and its important place in Texas history.